ARRANGEMENT OF FACILITIES IN THE SACRED AREA OF PURA BESAKIH AS A SUPPORTING FACTOR FOR HERITAGE TOURISM ATTRACTION IN KARANGASEM REGENCY, BALI - I Nengah Darma Yasa; Ida Ayu Tary Puspa (Adisam Publisher, 2025)
Besakih Temple is the largest temple complex located in Karangasem Regency, precisely in Besakih Village, Rendang District. Besakih Temple is one of the most important cultural sites and cultural conservation areas for the Balinese people, especially for the Hindu community in Bali. Many historical relics can be found at Besakih Temple, particularly regarding the development of Hinduism in Bali as well as the ancient Balinese Kingdom. Since 2022, the Regional Government, in collaboration with the Department of Public Works, has carried out a rearrangement of the facilities in the Besakih Temple area. This effort aims to facilitate visitors during their stay at the temple complex and to provide greater comfort both for the community conducting religious activities and for tourists. This study employs a qualitative method, with data obtained focusing on non-numeric information in the form of text, interviews, and observations, which are elaborated through verbal descriptions related to field findings. The data collection techniques used in this research include observation, interviews, literature study, and documentation. SWOT analysis was conducted to identify the strengths, opportunities, weaknesses, and threats of the facility arrangement at the Besakih Temple area. The method of data presentation applied in this study is a non-formal descriptive method, emphasizing the issues discussed. The results indicate that the arrangement of the Besakih Temple area has proven to support tourism activities, particularly heritage tourism in the Besakih area.